Perancangan Video Dokumenter Kuliner Legendaris di Kota Malang - Stefanus Wijaya; Didit Prasetyo Nugroho (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2019)
Malang City is a famous tourist city because of its nature tourism and also its culinary tour. There’s plenty of culinary spots in Malang City that has been around since 50 years ago and has become legendary. Even so, the lack of conservation efforts and knowledges will make these culinary spots to become forgotten. thus, there are appropriate alternative media that can be used to introduce these legendary culinary spots. One of them is documentary video. Qualitative method is used for this design, qualitative data is gathered through observation, interviews and documentation. This design’s output is a documentary video entitled “Legenda Kuliner Malang: Ragam Rasa Ragam Budaya” with 8 minutes 44 seconds duration, and a teaser with 32 seconds duration. The concept of this video is to show the connection between culinary and culture. Also some secondary output such as x-banner, cover and CD label, hat, totebag, sticker, t-shirt, and postcard.